(untitled) (Fiep Bulletin - online, 2013)
The osteoarthritis is a chronic and gradual rheumatic affection, Which characterizes for the loss of the joint cartilage. The theraputically applications of the laser in the physiotherapy include acceleration of the synthesis of collagem and reduction of the inflmmatory process. The study had the objective to verify the effect of the laser AsGaAl 830nm at 30mW on 4J/cm², as well as verifying the presence of placebos effect in this therapeutic pocess. The research was carried though in two stges: In beginning it was selected 100 volunteers, above of 60 years old, without pathological commitment, was collected the temperature of skin in the region of the knee. Later, it was selected 30 patients with osteoarthritis, which had been divided in two groups: G1 (treated) and G2 ( palcebo). It was evaluated pain intensity (EVA), flexion ampleness, edema and temperature of skin. Obtaining the following results: temperature without difference statistcs (p=0,99); Inclinometry (p=0,03), in favor of the laser. Paquimetry (p=0,04) for the laser. Pain without difference between groups p>0,05 (0,06). Through the analyzes of the data, is perceived these ran into the exposed theory in the consulted bibliographical referential, demonstrating that it is effient in the treatment of the osteoarthritis of knee, was verified the possible presence of placebo effect, once that was not studied the evolution of the osteoarthritis.